Parameters Suggesting Spontaneous Passage of Stones from Common Bile Duct: A Retrospective Study - Tawfik Khoury; Mohamed Adileh; Ashraf Imam; Yosef Azraq; Avital Bilitzky-Kopit; Muhamad Massarwa; Ari Benson; Zaher Bahouth; Samir Abu-Gazaleh; Wisam Sbeit; Rifaat Safadi; Abed Khalaileh (Canadian Journal of Gastroenterology and Hepatology)
Background. Common bile duct (CBD) stones are common. However, they are known to pass spontaneously, which obviates the need for ERCP. Aim. The aim of this study is to identify specific predictors for spontaneous passage of CBD stones. Methods. Data was retrospectively collected for all patients who were hospitalized with clinical, laboratory, or ultrasonographic evidence of choledocholithiasis and who underwent magnetic resonance cholangiopancreatography (MRCP) in Hadassah Medical Center between 2005 and 2011. The patients were classified into 4 groups: group A (positive MRCP and positive ERCP), group B (positive MRCP but negative ERCP), group C (positive MRCP but did not undergo ERCP), and group D (negative MRCP that did not undergo ERCP) for choledocholithiasis. All positive MRCP-groups (A+B+C) were further grouped together into group E. We compared groups A versus B and groups E versus D. Results. Comparing groups A versus B, only gamma-glutamyl transferase predicted spontaneous passage of stones from CBD, as the level was significantly higher in group A (677±12.1) versus group B (362.4±216.2) (P=0.023). Patients with small stone diameter (P=0.001), distal stones (P=0.05), and absence of intrahepatic dilatation (P=0.047) tend to pass their stones spontaneously. Comparing groups D versus E, it was found that male gender (P=0.03), older age (P<0.001), high levels of GGT (P=0.022), high levels of alkaline phosphatase (P=0.011), high levels of total bilirubin (P=0.007), and lower levels of amylase (P<0.001) are predictors for positive MRCP studies for CBD stones. Conclusion. Identification of specific predictors is important to avoid unnecessary invasive endoscopic intervention.